Features of financing investment projects of small and medium-sized businesses in Kazakhstan - Yerzhanova, S.K.; Aimyrzina, B.T.; Kamenova, M.Zh.; Jazykbayeva, B.K.; Ahmetova, D.T. (BUKETOV BUSINESS REVIEW, 2021)
Object: The article considers the issues of development of small and medium businesses as one of the significant elements for the effective functioning of economics aimed to create favourable conditions for developing domestic business. Methods: Small and medium businesses play an important role to ensure economic public involvement, tax payment into the budget, and social and economic development on the whole. The article describes the basic sources for financing investment projects of small and medium business entities, considers the condition of small and medium businesses in the Republic, analyzed the problems controlling the development, represented the author’s view for the solution. The authors research the sources for financial support of entrepreneurial development, the insufficiency problem, the lack of drivers for implementation. Based on the analyses of entrepreneurial activity in Kazakhstan for the last years conclusions and recommendations have been represented to improve economic levers of regulating entrepreneurship activities, the prognosis for the further development of small and medium businesses has been done. With the help of Desk Research, the basic indexes of small and medium business development and ways of financing small and medium businesses have been analyzed. Findings: Based on the regressive multiple data analyses and application of technical analysis, the amount of manpower employed in the small and medium business, the amount of GVA in the GDP (gross domestic product), the credit tranche, given to the small entrepreneurship, investments in the capital stock have been calculated. Conclusions: The necessity to deregulate business financially and legislatively has been justified. There have been worked out the practical recommendations to ensure refusal from the routine and specific random inspection visits. There also has been made an access to state and quasi-procurement together with the electronic trading platform, category system, and pre-qualified selection